Freedom and determinism - Campbell, Joseph Keim, 1958-; O'Rourke, Michael, 1963-; Shier, David, 1958- (Topics in contemporary philosophy., 2004)
This collection of contemporary essays by prominent contemporary thinkers on the topics of determinism and free agency concentrates primarily on two areas: the compatibility problem and the metaphysics of moral responsibility. There are also essays on the related fields of determinism and action theory. The book is unique in that it contains up-to-date summaries of the life-work of five influential philosophers: John Earman, Ted Honderich, Keith Lehrer, Robert Kane, and Peter van Inwagen. There are also contributions by other familiar and distinguished authors, including Richard Feldman, John Martin Fischer, Carl Ginet, and John Perry, as well as important rising philosophers. While most of the articles are written from a Western, analytic perspective, the volume includes a paper that addresses Buddhist perspectives on freedom of the will. With an opening essay written by the editors--"Freedom and Determinism: A Framework"--That sets the terms of the discussion, the book provides a remarkably comprehensive set of articles that are of value to a wide audience, from students of philosophy to scholars